Study of thermodynamic interaction parameters of poly(p-naphthalene-2(?) sulfonyl styrene) using inverse gas çhromatography - Kaya, Ismet; Demircilli, Kadir (My University, 1999)
We used the inverse gas chromatographic technique to find some thermodynamic parameters, such as average partial molar enthalpy, ?H?1, partial molar free energy. ?G?1 weight fraction activity coefficient. ???1 and the Flory-Huggins interaction parameter, ??12 for poly(p-naphthalene-2(?) sulfonyl styrene) organic solvents systems at infinite dilution. The values of ??12 found in this experiment were high for alkanes, o-xylene. and toluene, as is usual for polymer-nonsolvent systems, but were lower for alcohols, acetates, ketones, and benzene, as is usual for poly(p-naphthalene-2(?) sulfonyl stvrene) solvents systems. Similar results were obtained for ???1 in the same system. Additionally, the solubility parameter of poly(p-naphthalene- 2(?) sulfonyl styrene), were calculated as 6.75 (cal/cm3)0.5 and 6.81 (cal/cm3)0.5 from the slope or intercept of [formula omitted], at 180°C, respectively. © 2011, Walter de Gruyter GmbH & Co. All rights reserved.
Keywords: i.g.c. technique; polymer-solvent thermodynamic interactions